2022
DOI: 10.1007/s10584-022-03437-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for three distinct climate change audience segments with varying belief-updating tendencies: implications for climate change communication

Abstract: Mounting evidence suggests members of the general public are not homogeneous in their receptivity to climate science information. Studies segmenting climate change views typically deploy a top-down approach, whereby concepts salient in scientific literature determine the number and nature of segments. In contrast, in two studies using Australian citizens, we used a bottom-up approach, in which segments were determined from perceptions of climate change concepts derived from citizen social media discourse. In S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Kim et al (2013) confirmed that the use of social media could enhance the diversity of online communication and promote diverse activities in civic life, supporting the notion that social media has a positive impact on promoting civic engagement. Consequently, Andreotta et al (2022) investigated the link between using social media platforms such as Facebook, exposure to varying perspectives and the expansion of discussion networks' diversity. Additionally, a separate study (Kim and Kim, 2017) found a positive correlation among network diversity, social capital (bridging or bonding) and subjective well-being.…”
Section: Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al (2013) confirmed that the use of social media could enhance the diversity of online communication and promote diverse activities in civic life, supporting the notion that social media has a positive impact on promoting civic engagement. Consequently, Andreotta et al (2022) investigated the link between using social media platforms such as Facebook, exposure to varying perspectives and the expansion of discussion networks' diversity. Additionally, a separate study (Kim and Kim, 2017) found a positive correlation among network diversity, social capital (bridging or bonding) and subjective well-being.…”
Section: Heterogeneitymentioning
confidence: 99%
“…Potential research directions Psychology of cognitive biases on user perception (Andreotta et al, 2022;Barbera et al, 2015;Beck and Clark, 1997;De Zuniga et al, 2022;Lee, 2022;Messing and Westwood, 2012) User psychological profiles and perceptions of controversial issues Impact of selective exposure on polarization Emotional reactions to the event Cognitive de-biasing techniques development In-group and out-group affiliation Changes in user behavior Distorted view of reality, reinforcing stereotypes and deepening polarization Technical aspects of quantifying polarization (Barrett et al, 2021;Burgers et al, 2023;Grover et al, 2019;Lu et al, 2022;Modgil et al, 2021;Park, 2021;Tornberg, 2021) Influence of cognitive biases on people's reading and sharing behavior Fact-checking tools Polarization's impact on people's mental health Interventions to recognize and counteract biases Development and spreading of biases in digital communities AI and machine learning in studying bias-based polarization Inventions include mindfulness, cognitive behavioral therapy techniques, or metacognitive strategies Information system (IS) perspective on polarization (Allcott and Gentzkow, 2017, Au et al, 2021, Barfar, 2019Kaiser et al, 2022, Miller et al, 2022Vicario et al, 2019;Wang, 2015) Designing intelligent systems to mitigate polarization User interaction with personalized content The role of misinformation Longitudinal effects Evaluation of existing efforts The implications of decentralized social networks Comparative study across different platforms Management strategies on polarization (Feezell et al, 2021;Guan et al, 2023;Klein and Robison, 2019;Medaglia and Zhu, 2017) Reputation of organization in a polarized environment Education and media literacy Ethical considerations Crisis communication and response strategies for potential bias-based backlash Engagement management for balance among communities Internal communication and training to understand and recognize bias Content moderation and guidelines Source(s): Authors' own creation Table…”
Section: Perspectivesmentioning
confidence: 99%